The rough guide to classical music - Staines, Joe.; Buckley, Jonathan, 1956- (London : Rough Guides, 2010)
The ideal handbook on classical music. Both a CD guide and who's who, it covers a thousand years of music-- from Gregorian chant via Mozart and Schubert to contemporaries such as John Adams and Judith Weir.
Some earlier editions published as: Classical music : the rough guide
Previous ed.: 2005.
Includes bibliographical references and index.
Keywords: Music appreciation; Music -- Discography; Sound recordings -- Reviews; Music -- History and criticism; Composers -- Biography